Rekonfirmasi Identitas Nyai Di Pesantren: Reconfirmation of the Identity of Nyai in Islamic Boarding Schools - Syarifatul Marwiyah (Fenomena, 2016)
The leadership reconfirmation of Nyai (female leader) in pesantren (Islamic boarding school) remains a critical issue amid persistent patriarchal cultural biases that subordinate women's public roles. This study is grounded in the broader theoretical debate on gender equality within Islamic education, particularly the tension between normative religious interpretations and socio-historical contexts. The research aims to analyze the role of women's leadership in pesantren and to investigate the status of Nyai Rosyidah as a leader from the perspectives of the public and stakeholders at Pondok Pesantren Darus Sholah, Jember. A qualitative case study approach was employed, utilizing interviews, observations, and document analysis. The findings reveal that although Islam and Javanese philosophy provide space for female leadership, the community's acceptance remains fragmented. Specifically, three groups emerged: those who fully accept Nyai Rosyidah as a leader; those who reject female leadership entirely; and those who accept her but still prioritize male dominance. The study concludes that Nyai's leadership is not absolute and remains overshadowed by the Kyai's (male cleric) authority. It is recommended that pesantren develop more gender-just educational frameworks and that future research explores structural support systems for female leaders to strengthen their legitimacy beyond familial or substitute status. Rekonfirmasi kepemimpinan Nyai di pesantren menjadi isu krusial di tengah kuatnya bias budaya patriarki yang menomorduakan peran publik perempuan. Penelitian ini berpijak pada peta besar perdebatan kesetaraan gender dalam pendidikan Islam, khususnya ketegangan antara penafsiran normatif dan konteks sosio-historis. Tujuan penelitian adalah menganalisis peran kepemimpinan perempuan di pesantren dan mengkaji status Nyai Rosyidah sebagai pemimpin menurut pandangan publik dan pemangku kepentingan di Pondok Pesantren Darus Sholah, Jember. Metode yang digunakan adalah studi kasus kualitatif melalui wawancara, observasi, dan analisis dokumen. Hasil penelitian menunjukkan bahwa meskipun Islam dan filsafat Jawa memberikan ruang bagi kepemimpinan perempuan, penerimaan masyarakat tetap terfragmentasi menjadi tiga kelompok: kelompok yang menerima penuh kepemimpinan Nyai Rosyidah; kelompok yang menolak; dan kelompok yang menerima namun tetap mengunggulkan dominasi laki-laki. Kesimpulannya, kepemimpinan Nyai tidak bersifat mutlak dan masih berada dalam bayang-bayang otoritas Kyai. Rekomendasinya, pesantren perlu mengembangkan kerangka pendidikan yang berkeadilan gender, serta diperlukan penelitian lebih lanjut tentang sistem pendukung struktural bagi pemimpin perempuan agar legitimasi mereka tidak hanya berbasis status substitusi atau familial.